Pyrazole; A Privileged Scaffold of Medicinal Chemistry: A Comprehensive Review - Kumar, Ram; Sharma, Raksha; Sharma, Dinesh K. (Current Topics in Medicinal Chemistry, 2023)
Pyrazole is considered an important active scaffold that possesses various types of pharmacological activities. The overwhelming literature reported earlier reflects the immense biological potential of pyrazole derivatives. The presence of this moiety in various FDA-approved drugs, including celecoxib (anti-inflammatory), apixaban (anticoagulant), rimonabant (anti-obesity), difenamizole (analgesic), and sildenafil (for erectile dysfunction), has proved its pharmacological potential. Owing to its diversity in the biological field, this nucleus has attracted the attention of many researchers to study its skeleton chemically and biologically. This review highlights the literature supporting the research of the past 10 years related to the structures of pyrazole derivatives with their corresponding biological activities. The findings of this review may open new avenues for an upcoming scientific breakthrough.
Keywords: Biological activity